Cucurbitaceae Glycosides: An In-depth Review on its Source, Structural, and Medicinal Significance - Mulay, Vallabh; Desikan, Rajagopal (Current Traditional Medicine, 2025)
BackgroundThe Cucurbitaceae family has been well-known since ancient times for its use in daily food preparations. Various traditional medicinal systems have also recognized its therapeutic importance. Its significance has also been established by modern techniques.ObjectiveThe current review aims to emphasize the glycosides of the Cucurbitaceae family in terms of their source, structures, extraction media, and bioactivities in various therapeutic areas like anti-inflammatory, anti-bacterial, anti-cancerous, anti-diabetic, and cardiac models. Glycosides of Cucurbitaceae have been studied extensively. However, considering the vastness of the diversity among this family; there are still various avenues in which further research work is needed.MethodsFor the present review, we used Elsevier-ScienceDirect, SpringerLink, PubMed, ArticlesPlus, Semantic Scholar, and Google Scholar to conduct a literature search.ResultsCucurbitaceae is enriched with secondary metabolites, mainly glycosides. The occurrence of glycoside with its species, along with plant parts, is crucial and elaborately covered. It also captures the extraction system. The structure of selected glycosides is represented along with respective references. Various studies elaborate on the pharmacological significance of the extracts in diverse therapeutic areas.ConclusionThis review provides extensive aspects about the glycosides of the family Cucurbitaceae and will help in further exploration of extraction, isolation, and bioactivity studies of this important class of compounds from one of the largest families, i.e., Cucurbitaceae. It reiterates the need for further exploration in standardization along with extensive safety and efficacy studies.
Keywords: phytochemistry